2016
DOI: 10.1098/rspb.2015.2980
|View full text |Cite
|
Sign up to set email alerts
|

Palenque de San Basilio in Colombia: genetic data support an oral history of a paternal ancestry in Congo

Abstract: The Palenque, a black community in rural Colombia, have an oral history of fugitive African slaves founding a free village near Cartagena in the seventeenth century. Recently, linguists have identified some 200 words in regular use that originate in a Kikongo language, with Yombe, mainly spoken in the Congo region, being the most likely source. The non-recombining portion of the Y chromosome (NRY) and mitochondrial DNA were analysed to establish whether there was greater similarity between present-day members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 51 publications
4
17
0
1
Order By: Relevance
“…In the present study, we analysed numerous Y chromosome-specific markers and extended the mtDNA analysis to the whole CR, enabling a clear assignment of the continental origin of the lineages in Palenque. www.nature.com/scientificreports/ A high African maternal ancestry was found, in accordance with the report by Ansari-Pour et al 12 . Nevertheless, it was not possible to perform a straightforward comparison between the two studies, since previous data included only HVSI information, and many samples could not be assigned to a specific haplogroup, namely, inside some African and Native American branches.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we analysed numerous Y chromosome-specific markers and extended the mtDNA analysis to the whole CR, enabling a clear assignment of the continental origin of the lineages in Palenque. www.nature.com/scientificreports/ A high African maternal ancestry was found, in accordance with the report by Ansari-Pour et al 12 . Nevertheless, it was not possible to perform a straightforward comparison between the two studies, since previous data included only HVSI information, and many samples could not be assigned to a specific haplogroup, namely, inside some African and Native American branches.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, several communities tracing their ancestry to marooned slaves have been prime objects of study in multidisciplinary analyses examining the origin in Africa of the slaves who were transported to America (68,84,96). Genetic studies have shown that, although many of these populations have mainly African ancestry (8,68), some have substantial non-African admixture, indicating that contrary to what was previously thought, maroon settlements were not always that isolated (84).…”
Section: Special Populations In the Americasmentioning
confidence: 75%
“…To evaluate the genetic composition and stratification of the Colombian population, several studies have been performed using different types of ancestry and forensic markers in different populations throughout the country (Alonso Morales et al, 2018; Alonso & Usaquén, 2012; Ansari‐Pour et al, 2016; Bedoya et al, 2006; Bortolini, Salzano, & Thomas, 2003; Carvajal‐Carmona et al, 2000; Garavito et al, 2015; Ibarra et al, 2014; Martínez et al, 2017; Mesa et al, 2000; Noguera et al, 2014; Ossa et al, 2015, 2016; Rodas, Gelvez, & Keyeux, 2013; Rojas et al, 2010; Rojas, Roa, Briceño, Guaneme, & Gómez, 2011; Urbano, Portilla, Builes, Gusmão, & Sierra‐Torres, 2016; Xavier et al, 2015; Yunis, Acevedo, Campo, & Yunis, 2013). These studies showed that urban populations have high levels of non‐native admixture, and Native American, African, and European ancestries vary across the country.…”
Section: Introductionmentioning
confidence: 99%